Analisis Komitmen dan Kompensasi terhadap Efektivitas Kerja: Studi Empiris pada Aparatur UPTD Puskesmas Bojong Rawalumbu (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of work commitment and compensation on employee work effectiveness at UPTD Puskesmas Bojong Rawalumbu. An explanatory quantitative approach was used with a total sampling technique involving 33 employees. Primary data were gathered via questionnaires and analyzed using multiple linear regression. The results indicate that work commitment and compensation simultaneously have a significant impact on work effectiveness, explaining 55.4% of the variance. Partially, work commitment has a positive and significant effect on work effectiveness, while compensation does not show a significant effect. These findings suggest that public health sector apparatuses are driven more by intrinsic motivation and professional dedication than financial incentives. This study is limited by its small sample size and single-site setting, which may restrict the generalizability of the findings. Future research is recommended to expand the sample across multiple health centers and incorporate additional variables such as employee well-being, burnout, and servant leadership to more comprehensively explain work effectiveness in public sector organizations.